Description of Paravulvus moroccanus sp. n. (Nematoda, Dorylaimida, Nygolaimidae) from the High Atlas Mountains, Morocco, with notes on the taxonomy of the genus - Gilarte, Patricia; Carreira, José Antonio; Peña-Santiago, Reyes (Zootaxa, 2013)
Paravulvus moroccanus sp. n., collected in the Moroccan eastern High Atlas, is described and illustrated.  The new species is characterized by its 1.06–1.36 mm long body, lip region offset by marked depression and 11–13 µm broad, mural tooth solididentoid and 5.5–6.5 µm long, neck 229–270 µm long, pharyngeal expansion 108–126 µm long or occupying less than one-half (42–48%) of total neck length, uterus 27–47 μm long or 0.7–1.1 times the corresponding body diameter, V = 46–56, paravulvae absent, female tail rounded conoid (21–27 µm, c = 42–64, c’ = 1.1–1.5), and male unknown. The taxonomy of Paravulvus is updated, with comments on its definition, a discussion of its relationships, and the provision of a list of species along with a key to their identification and a compendium of their morphometrics.